1989
DOI: 10.1002/j.1460-2075.1989.tb08560.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical recognition of the palindromic AP1 binding site (TRE) by Fos protein complexes.

Abstract: Fos and Jun proteins form a tight complex which binds specifically to the AP1 recognition sequence, a palindromic DNA element also referred to as the TPA responsive element (TRE). To elucidate the mechanism of Fos‐Jun interaction with the TRE we have performed UV cross‐linking studies using oligonucleotides where thymines were replaced with bromouracil. Our results indicate that both Fos and Jun directly contact the TRE but that the interaction of Fos and Jun with thymines in structurally equivalent positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 36 publications
8
94
0
2
Order By: Relevance
“…Binding to this site resulted in two specific complexes (Fig. 6), as reported in the literature (27,34). Further, specific binding to this AP-1 element was increased in extracts isolated from TCDD-treated NHK cultures.…”
Section: Fig 3 Atra Abolishes Tcdd-induced Binding To the Cyp1a1supporting
confidence: 81%
“…Binding to this site resulted in two specific complexes (Fig. 6), as reported in the literature (27,34). Further, specific binding to this AP-1 element was increased in extracts isolated from TCDD-treated NHK cultures.…”
Section: Fig 3 Atra Abolishes Tcdd-induced Binding To the Cyp1a1supporting
confidence: 81%
“…5, lanes 1 to 6) (Fig. 6, lane 4) It has been demonstrated that, for binding of Fos-Jun heterodimer to TRE, each of the two proteins recognizes a half site of its recognition sequence (51,62). We have established in this study that DNA-binding specificities of the Maf-Maf and Jun-Jun homodimers are clearly different.…”
Section: Methodsmentioning
confidence: 54%
“…4 and 6A). To further analyze the possible role of this putative AP-1 binding site, we made two types of mutation, preventing Jun and Fos binding (33). The first mutation (4551 AP-1 mut 1) was introduced either in the 4551 CAT DNA or in the 4551 FP2 del plasmid.…”
Section: None Of the Putative Retinoic Acid Response Elements (Rares)mentioning
confidence: 99%